Perspective on strategies for matching across age and sex in physiology research: “recreationally active” is not good enough - Schweitzer, Allyson M.; Fuller, Daniel; Fliss, Matthew D.; Mitchell, Cameron J. (Frontiers in Physiology, 2025)
Cardiorespiratory fitness (CRF) and muscular fitness are powerful confounders in age and sex-related comparisons. This paper provides a perspective on the benefits and limitations of matching participants by physical activity behaviour, objectively measured fitness and normative fitness percentiles. Data presented herein are a subset of a larger study, and highlight that matching by physical activity, does not necessarily match on other metrics like physical fitness, especially when age-related comparisons are being made. Our data showed that young and older adults matched by physical activity behaviours showed the expected higher CRF and muscular fitness in male and younger participants, but older adults had higher CRF percentiles. This suggests that matching by physical activity behaviour may select older adults with relatively higher CRF. Researchers must choose their matching method carefully to ensure the appropriate aspects of fitness have been matched between groups. For clarity, they should also report when certain aspects of fitness have not been accounted for and give an explanation as to why.